Efficacy of Journal as Free-Writing Technique: A Study of Saudi EFL Learners’ Performance - Dr. Shahzad ul Hassan Farooqi (University of Chitral Journal of Linguistics and Literature, 2023)
This article is based on a longitudinal writing program to evaluate the efficacy of Journal as a viable free-writing technique in Saudi EFL scenario. Data taken from 54 students of English language major at a Saudi university is studied. Forty-five students participate in a six-week-long program during which an hour-long session is held every week. Students choose topics of their own interest, along with some prompts from teachers to write in English without fear of committing errors. A correlation is sought between fluency (measured in terms of the number of lines) and the number of errors. Results show an increase of written lines from an average of 9.86 to 15.24 lines per journal while a sharp decrease is observed in spelling errors from 6.1 per journal to 3.28. Capitalization errors also show a steep decline from 3.2 per journal to 0.33. A similar downward pattern is observed in the case of period (full stop) related errors whose average is noted 1.77 per journal initially and 0.86 by the end. Errors related to the subject-verb agreement also show a sharp dip from 3.42 to 1.83 till the middle of the program, however, move up to 3.61 which suggests that it is an area where Saudi EFL learners need more attention. The study shows that journal writing helped in improving writing output and controlling errors without being bogged down by the fear of error hunting. Students also showed 68.8 percent approval of free-writing journal as a viable technique to improve writing skill.